Effect of Dry Heat Application on Perineal Pain and Episiotomy Wound Healing among Primipara Women - Naglaa Zaki Hassan Roma; Rasha Mohamed Essa; Zohour Ibrahim Rashwan; Afaf Hassan Ahmed (Hindawi Limited, 2023)
Background. Women who undergo perineal episiotomy can be affected by several complications such as bleeding, infection, perineal pain, dyspareunia, reduction of sexual desire, as well as urinary and anal incontinence. Perineal pain related to episiotomy has been reported to interfere with women's daily activities postpartum and can prevent proper breastfeeding, proper rooming-in, and maternal-infant bonding. The purpose of this study was to determine the effect of dry heat application on perineal pain and episiotomy wound Healing among primipara women. Method. A quasi-experimental, two-group, pre-post-test research study was conducted at the postnatal inpatient ward and the outpatient clinic of the El-Shatby Maternity University Hospital in Alexandria. A sample of 100 parturient women was divided into the following two groups at random: dry heat and moist (control) heat. Women in the moist heat group were advised to sit in a basin (tub) of warm water for 10 minutes, while those in the dry heat group were instructed to set an infrared light (230 volts) at a distance of 45 cm from the perineum after 12 hours post episiotomy. Both interventions were applied twice a day for ten consecutive days. They evaluated the severity of their perineal pain at baseline and repeated it on the 5th and 10th days after obtaining the interventions while the episiotomy wound healing was assessed on the 5th and 10th days. Results. It was discovered that the dry heat group had a significantly improved episiotomy wound healing as regards perineal redness, edema of the perineal area, ecchymosis, wound discharge, and approximation of wound edges on the 5th (P<0.001, P<0.001, P<0.007, P<0.003, and P<0.001, respectively) and 10th day after intervention (P<0.001, P<0.001, P<0.001, P<0.005, and P<0.001, respectively) than the moist heat group. The primipara women had significantly lower perineal pain intensity in the dry heat group on the 5th and 10th days after intervention than in the moist heat group (MHP<0.001 for the dry heat group and MHP=0.004 for the moist heat group). Conclusion. The application of dry heat promoted episiotomy wound healing among primipara women and reduced their perineal pain during early postpartum days than moist heat.